Efficient synthesis of phenylene-ethynylene rods and their use as rigid spacers in divalent inhibitors - Pertici, Francesca; Varga, Norbert; van Duijn, Arnoud; Rey-Carrizo, Matias; Bernardi, Anna; Pieters, Roland J. (Beilstein Journal of Organic Chemistry, 2013)
The synthesis of phenylene-ethynylene rods and their use as rigid spacers is described. Alternation of a Sonogashira reaction and silyl group cleavage was used to obtain rigid spacers with even and odd numbers of phenylene units. Preliminary applications of these rods in divalent systems are shown. Inhibition studies with Pseudomonas Aeruginosa lectin LecA showed that the rigid spacer proved greatly beneficial for the inhibitory potency.
Keywords: multivalent carbohydrates; LecA inhibition; phenylene ethynylene; rigid spacers; Sonogashira reaction